PEMODELAN SINYAL GETARAN YANG DISEBABKAN OLEH CACAT PADA RING LUAR DARI BANTALAN SILINDER - Cahaya Ramadhan; Achmad Widodo; Djoeli Satrijo (JURNAL TEKNIK MESIN, 2013)
Roller bearing is a very important component for almost all forms of machinery. Because of the widespread use and importance, their failure is most often the cause harm and breakdown. Diagnosis of damage to rolling element bearing usually done using vibration analysis with the detect the characteristic frequency of bearing defect generated due to interaction with the rolling elements. This study was conducted to model and diagnose cylindrical bearing damage. An analysis of vibration signals from a rolling element defect through a single point on the outer ring bearing cylinder using ANSYS FEA software has been done. Bearing is modeled and compared with bearing without defect with the bearing who have a variety of different defect sizes. Defects makes the vibration signal that occurs in the outer ring cylindrical bearing without defect and with defect produce differences in peak amplitude.